Coverage of titles in Central Asian Hellenistic Sources (Eurasian Journal of History, Geography and Economics, 2022)
The article covers numismatic and written sources on the names of the Hellenistic states of Central Asia, the name of the king, the title adopted, the image of the king, the time of his accession to the throne and religious views through numismatic sources.The article used historical comparative, critical, logical, logical and chronological, semantic and pragmatic analysis methods.The difficulty in studying these titles is the lack of data. In the article, the titles of the Hellenistic period were studied on the basis of more numismatic sources